Bases para la implementación de la norma ISO 14001 en la empresa Petrosan Services SAS (2020)
Throughout the following work, a diagnostic exercise is developed and later a proposal for an environmental management program is proposed, which seeks to implement the bases for the ISO 14001 standard, in a company dedicated to the design, construction and assembly of oil & gas production facilities, called PETROSAN SERVICES S.A.S. The investigation as a starting point was carried out by applying an initial environmental review, through checklists focused on environmental activities and implementation of the environmental management system. The checklists were completed by the organization’s senior management. As a result, the priority environmental aspects due to the pollution generated by the company's activities were identified, thus following what is established by the ISO 14001 standard, as the basis for the implementation of the project. Subsequently, the proposal for the implementation of the environmental management program was made, based on three main aspects, which are, reduction of soil contamination, disposal and efficient use of water and adequate disposal of solid waste.